Subclinical Target Organ Damage in a Sample of Children with Autosomal Dominant Polycystic Kidney Disease: A Pilot Study - Simone Romano; Denise Marcon; Lorella Branz; Angela Tagetti; Giada Monamì; Alice Giontella; Francesca Malesani; Luca Pecoraro; Pietro Minuz; Milena Brugnara; Cristiano Fava (Medicina, 2023)
Background and Objectives: Hypertension and vascular damage can begin in adolescents affected by Autosomal Dominant Polycystic Kidney Disease (ADPKD). This study aimed to evaluate markers of vascular damage and left ventricular geometry in a sample of children with ADPKD. Materials and Methods: Several vascular measurements were obtained: ambulatory blood pressure monitoring (ABPM), carotid intima-media thickness (cIMT), carotid distensibility coefficient (cDC), pulse wave velocity (PWV), and echocardiographic measurements (relative wall thickness (RWT) and left ventricular mass index (LVMI)). Results: Eleven ADPKD children were recruited (four females and seven males, mean age 9.5 ± 3.2 years). Four children were hypertensive at the ABPM, five were normotensive, and for two ABPM was not available. RWT was tendentially high (mean 0.47 ± 0.39). Eight patients had concentric cardiac remodeling, while one patient had cardiac hypertrophy. cIMT was above the 95° percentile for sex and height in 80% of the children (0.5 ± 0.005 mm). The average PWV and cDC were between the normal range (5.5 ± 4.6 m/s and 89.6 ± 16.1 × 10−3/KPa, respectively). We observed a positive correlation between the PWV and RWT (r = 0.616; p = 0.044) and a negative correlation between cDC and RWT (r = −0.770; p = 0.015). Cardiovascular damages (cIMT > 95° percentile) were found in normotensive patients. Conclusions: Increased RWT and high cIMT, indicating subclinical organ damage, are already present in ADPKD children. RWT was significantly correlated to that of cDC and PWV, implying that vascular stiffening is associated with cardiac remodeling. None of the children had an alteration in renal function. Subclinical cardiovascular damage preceded the decline in glomerular filtration rate.